Views and preferences of medical professionals and pregnant women about a novel primary prevention intervention for hypertensive disorders of pregnancy: a qualitative study - A. Vestering; M. N. Bekker; D. E. Grobbee; R. van der Graaf; A. Franx; N. M. T. Crombag; J. L. Browne (BMC, 2019)
Abstract Background Calcium and low-dose aspirin are two potential approaches for primary prevention of hypertensive disorders of pregnancy (HDP). This study aimed to explore the acceptability, views and preferences of pregnant women and primary healthcare providers for a fixed-dose combined preparation of aspirin and calcium (a polypill) as primary prevention of HDP in an unselected pregnant population. Methods In this qualitative study eight in-depth semi-structured interviews were conducted with Dutch primary care midwives and general practitioners. Seven focus group discussions were organised with women with low-risk pregnancies. Topics discussed were: perceptions of preeclampsia; information provision about preeclampsia and a polypill; views on the polypill concept; preferences and needs regarding implementation of a polypill. Thematic analysis of the data transcripts was carried out to identify emerging themes. Results Two major themes shaped medical professionals' and women's views on the polypill concept: 'Informed Choice' and 'Medicalisation'. Both could be divided into subthemes related to information provision, personal choice and discussions with regard to the balance between 'unnecessary medicalisation' and 'scientific progress'. Conclusions In general, women and healthcare practitioners expressed a positive attitude towards a polypill intervention as primary prevention strategy with aspirin and calcium, providing some conditions are met. The most important conditions for implementation of such a strategy were safety, effectiveness and the possibility to make a well-informed autonomous decision.